"My miracle child": Experiences of families with children born at 23-24 weeks of gestation: A qualitative descriptive study - Väliaho, Anniina (fi=Turun yliopisto|en=University of Turku|, 2025)
Preterm survivors born at 23 and 24 weeks are a growing population. However, the risks for health and developmental consequences increase the earlier a child is born. It is also known that the birth of a child extremely preterm, as well as the possible long-term morbidities of a preterm-born child, pose a challenge for the parents. The aim of this qualitative thesis was to explore the experiences of families with children born at 23–24 weeks of gestation. Using a qualitative description approach and a semi-structured interview, 29 mothers and eight fathers of children born at 23–24 weeks of gestation were interviewed. In addition, 18 children and adolescents born at 23–24 weeks of gestation were interviewed. The children were born in between 2002-2014 and had received active neonatal care. The interviews were thematically analysed. The results showed that the mothers’ accounts described the lives of their children born at 23 weeks of gestation as active and rich, even in the midst of the children’s long-term health and learning challenges. The mothers were dedicated to parenting and they also expressed feelings of gratitude. Parents of children born at 23–24 weeks, when describing retrospectively the bonding process between themselves and their infant, had often experienced the bonding as natural or even easy, despite the traumatic start to parenthood. Support from NICU staff, participation in infant care, parent-infant physical closeness and earlier parental experience were reported to enhance the bonding process. In the preterm survivors’ interviews, the children and adolescents exhibited different perspectives in terms of how they had experienced the effects of their extremely premature birth: from reporting no effects at all to identifying some small or moderate, mostly physical health-related challenges. One group of children did not connect their challenges to prematurity or overall reflected very little on their prematurity. The results from this thesis highlight the need to include both parental perspectives as well as preterm survivors’ own experiences to assess neonatal care and its outcomes.

23–24 raskausviikoilla syntyvät keskoset ovat kasvava ryhmä. Keskosuuteen liittyvien terveys- ja kehityshaasteiden riski on sitä suurempi, mitä varhaisemmilla viikoilla lapsi on syntynyt. Tiedetään myös, että hyvin ennenaikaisen keskoslapsen syntymä haastaa vanhemmuutta, samoin kuin keskosuuteen liittyvät pitkäaikaiskehityksen ongelmat. Tämän väitöskirjan tavoitteena oli kartoittaa 23–24 raskausviikoilla syntyneiden keskosten ja heidän perheidensä kokemuksia. Työ toteutettiin käyttäen laadullista tutkimusotetta (kvalitatiivinen deskriptio) ja menetelmänä oli puolistrukturoitu haastattelu. Tutkimuksessa haastateltiin 29 äitiä ja kahdeksan isää, jotka olivat 23– 24 raskausviikoilla syntyneiden keskoslasten vanhempia. Lisäksi haastateltiin 18 lasta ja nuorta, jotka olivat syntyneet 23–24 raskausviikoilla, ja saaneet aktiivihoitoa Turun yliopistollisessa keskussairaalassa vuosina 2002-2014. Haastattelut analysoitiin temaattisesti. Tulokset osoittivat, että äidit kuvasivat 23 raskausviikolla syntyneiden lasten elämää aktiivisena ja rikkaana, vaikkakin lapsilla oli pitkäaikaisia terveyden ja oppimisen ongelmia. Äidit kuvautuivat vanhemmuudelle omistautuneina, ja he myös ilmaisivat kiitollisuuden tunteita. 23–24 raskausviikoilla syntyneiden lasten vanhempien kuvauksissa varhaisen tunnesiteen muodostumisesta korostui suhteen rakentumisen luonnollisuus vanhemmuuden traumaattisista alkuvaiheista huolimatta. Keskolan henkilökunnan tuki, vauvan hoitoon osallistuminen, läheisyys vauvan kanssa sekä aiempi kokemus vanhemmuudesta olivat tukeneet suhteen rakentumista. Keskosina syntyneiden lasten ja nuorten kokemuksissa ilmeni erilaisia tapoja hahmottaa erittäin ennenaikaisen syntymän vaikutuksia: osa ei ilmaissut kokeneensa keskosuuden vaikuttavan lainkaan, osa kuvasi lieviä tai kohtalaisia, useimmiten fyysiseen terveyteen liittyviä haasteita. Yksi lapsiryhmä ei yhdistänyt haasteita keskosuuteen tai tuotti muuten hyvin vähän reflektiota. Väitöskirjan tulokset korostavat niin vanhempien kuin keskosena syntyneiden omien kokemusten tärkeyttä keskoshoidon käytäntöjen ja tulosten tutkimuksen osaalueena.
Keywords: qualitative study; extremely preterm; parenting